Analysis of the Thermogenic Gas Source of Natural Gas Hydrates Over the Dongsha Waters in the Northern South China Sea - Feng, Changmao; Zhong, Guangjian; Sun, Ming; Lei, Zhenyu; Yi, Hai; Zhao, Zhongquan (Frontiers in Earth Science, 2022)
Gas hydrates were newly discovered in the Dongsha Waters of the South China Sea by drilling in 2013 and 2019. The drilling results show that the hydrates consist of microbial gas and thermogenic gas, but the source layers of the thermogenic gas are not clear. The Chaoshan depression is the largest relict Mesozoic basin under the Dongsha Waters where thick T3—K strata, up to 5000 m, have developed under thin Cenozoic sediments. The T3—J1 and J3 bear the two main layers of hydrocarbon source rocks rich in II2-III type organic matter, mainly in the western sag, the middle low bulge, and the eastern sag. The T3—J1 developed bathyal - neritic mud rocks, generally greater than 400 m in thickness. The J3 mainly developed closed and semi-closed bay type mud, also II2-III type. Nowadays these two layers are in their mature - over mature stages, thus potentially high-producing. There have developed deep faults cutting through the Mesozoic strata and distributing fractures within the Cenozoic sediments. Analysis of geochemical and geological samples dredged from the seabed indicates a significant oil and gas leakage activity well correlated spatially with the Mesozoic-associated faults. The association of fault-fractures can act as good channels for the thermogenic gas to move upward and diffuse into the temperature pressure stabilization zone of the hydrate. Thus, sufficient gas from the Mesozoic production layers is deemed the main source of thermogenic gas. The area where the Mesozoic faults are activated is the main leakage area of thermogenic gas, thus the main target for future hydrate exploration.